Knockdown of LINC00511 enhances radiosensitivity of lung adenocarcinoma via regulating miR-497-5p/SMAD3. Issue 1 (31st December 2023) - Li, Chongxin; Fu, Yanyan; He, Yongmei; Huang, Nan; Yue, Jun; Miao, Yi; Lv, Jialing; Xiao, Youchuan; Deng, Ruoyu; Zhang, Chao; Huang, Meifang
ABSTRACT: As the most common histological subtype of primary lung cancer, lung adenocarcinoma (LUAD) causes enormous cancer deaths worldwide. Radiotherapy has been frequently used in LUAD cases, and radiosensitivity is vital for LUAD therapy. This research sought to explore the genetic factors affecting radiosensitivity in LUAD and inner mechanisms. LINC00511, miR-497-5p, and SMAD3 expression in LUAD cells were detected via qRT-PCR and western blot. CCK-8 assays, colony formation, and flow cytometry assays were employed to explore the cell viability, apoptosis, and radiosensitivity in PC-9 and A549 cells. The targeting relationship between LINC00511, miR-497-5p, and SMAD3 was verified by dual luciferase reporter assay. Furthermore, xenograft experiments were performed for the in vivo verification. In conclusion, LINC00511 was overexpressed in LUAD cells, which downregulated downstream miR-497-5p expression and mediately led to SMAD3 activation. LINC00511 downregulation suppressed cell viability while enhanced apoptosis rate in LUAD cells. Also, LINC00511 and SMAD3 were overexpressed, while miR-497-5p was downregulated in LUAD cells exposed to 4Gy irradiation treatment. Moreover, LINC00511 inhibition could block SMAD3 expression and promoted the radiosensitivity both in vitro and in vivo. These findings uncover LINC00511 knockdown promoted miR-497-5p expression and subsequently led to lower SMAD3 level, which enhanced radiosensitivity in LUAD cells. LINC00511/miR-497-5p/SMAD3 axis could be of considerable potential to enhance radiosensitivity in LUAD.